Tourism Destination Development Strategy in North Sulawesi - Bahri, Efri Syamsul; Tenda, Mirjam Pratidina (International Journal of Strategic Studies, 2024)
Tourist Destinations are one of the mainstays of North Sulawesi Province in achieving regional income. The strategy for developing Tourist Destinations in the region needs to be carried out to increase contributions to regional development, improve quality, and improve community welfare. This study aims to identify strategies for developing Tourist Destinations in North Sulawesi. This study uses a qualitative method with a descriptive approach. Furthermore, this study also uses a literature study approach. Research reference data was obtained from journal literature and reference books related to the strategy for developing Tourist Destinations in North Sulawesi. The study found four strategies for developing Tourist Destinations in North Sulawesi: sustainability, environment, economy, and socio-culture. The Government, the Regional Government of North Sulawesi Province, and stakeholders in developing Tourist Destinations can optimize the implementation of the strategies identified in this study to optimize the development of Tourist Destinations in North Sulawesi.